Evolutionary patterns of cranial ontogeny in Sigmodontines (Rodentia, Cricetidae). (25th September 2021) - Segura, Valentina; Flores, David; Jayat, Pablo; Martin, Gabriel
Abstract: Sigmodontines comprise one of the most diverse radiations of mammals. The cranial ontogeny has been studied in several mammals, but remains poorly studied in the group. We quantified the ontogenetic pattern for 22 sigmodontine species and 8 outgroups, generating partial reconstructions of ancestral allometric growth patterns, and testing the role of evolutionary history on cranial ontogeny. Sigmodontines were conservative in growth pattern, without unique patterns defining tribes. The allometric growth of the cranium was mostly negative, with Akodontini being the most isometric and Phyllotini the most allometric tribes. Allometry of variables associated with the neurocranium was mostly negative, while those linked to trophic functions showed positive allometry or isometry. A general cranial lengthening was detected, but variables associated with cranial width or height grew at lower rates. Cranial growth and development were associated with changes in the musculature functionally involved in bite and mastication. Most changes occurred in earlier postnatal stages, achieving an early morphological optimum. Few changes in the rate of growth at internal nodes were detected, and the stasis along the backbone was recurrent. Cranial elongation was a pattern widespread in the sample and likely a plesiomorphic condition. The few synapomorphies defining the ancestor of Sigmodontinae conform to a pattern with zygomatic arches little expanded laterally and globose braincases. The conservative pattern may be attributed to the biomechanically optimal morphology for omnivorous diets, suggesting that the generalized morphology allows the exploitation of multiple types of food with minor morphological adjustments. Abstract : In this report, we quantified the cranial ontogeny of sigmodontine rodents rebuilding their ancestral growth pattern and testing the role of evolutionary history on cranial ontogeny. Sigmodontines were conservative without unique patterns defining tribes. Cranial elongation was a widespread pattern and likely a plesiomorphic condition. Few synapomorphies defined the ancestor of Sigmodontinae, suggesting a biomechanically optimal morphology for omnivorous diets that allows them the exploitation of multiple types of food, with minor morphological adjustments.